Effect of Oral Administration of Mytragina Speciosa on Blood Ketone Level and Glomerular Histology in Streptozotocin Induced Diabetic Mice - choirotussanijjah, Choirotussanijjah; Salim, Hotimah Masdan; Bintarti, Tri Wahyuni; Irawan, Danny (Jurnal Medis Islam Internasional, 2024)
Introduction: Diabetes mellitus is a chronic metabolic disease characterized by increased sugar levels that cause serious damage to various organs. Diabetic ketoacidosis is one of the complications of diabetes mellitus. It is characterized by a decrease in the patient's consciousness, increased blood sugar levels, and the presence of acidic ketone bodies. It is a serious condition that can cause a coma or even death. Mytragina Speciosa,  known as kratom, is a plant often found in Southeast Asia, including Indonesia. This herb is frequently used as a stimulant to treat fatigue and help improve productivity. Based on previous research, Mytragina Speciosa is rich in alkaloids, flavonoids, and phenols. These compounds are very useful for inhibiting the activity of α-glucosidase and lipase enzymes in the pancreas, so they have a potential effect on diabetes mellitus. However, there has been no research related to the administration of Mytragina Speciosa its effect on blood ketone levels and glomerular diameter. Objective: to determine whether there is an effect of Mytragina Speciosa on blood ketone levels and glomerular diameter in mice with a diabetes mellitus model. Methods: Hyperglycemia is induced by Streptozotocin. On the 14th day, the mice will be checked for hyperglycemia and blood ketone levels. Administration of Mytragina Speciosa begins on day 15 for 2 weeks. At the end of the second week, the mice will be checked for blood ketone levels using a special kit to detect ketone bodies. Furthermore, the glomerular diameter will also be assessed. Results: In this study, treatment for 2 weeks only caused an increase in blood sugar levels in mice, but did not cause an increase in blood ketone levels in the diabetes group or other treatment groups (p > 0.05). Histological preparation of the Glomerulus showed a decline in glomerular diameter. Conclusions: The administration of Mitragyna speciosa extract did not result in a significant increase in blood ketone levels in diabetic mice. Many factors are involved in increasing blood ketone. It is necessary to monitor ketone levels during treatment as well as have a longer treatment time to see the effect of Mitragyna speciosa on ketones